Spectral domain optical coherence tomography findings predicting visual outcome in patients with rhegmatogenous retinal detachment undergoing retinal detachment surgery - Pankti Shah; Tejas H Desai (Journal of Clinical Ophthalmology and Research)
Purpose: The purpose of the study was to investigate spectral domain optical coherence tomography (SD-OCT) findings as predictors of visual outcomes in patients undergoing retinal detachment (RD) surgery for rhegmatogenous RD (RRD). Materials and Methods: A prospective study was conducted on 50 eyes diagnosed with RRD, aged between 10 and 80 years, who underwent RD surgery at a tertiary eye care hospital between September 2018 and February 2020. Comprehensive ophthalmic evaluations were performed, and SD-OCT images were analyzed in addition to clinical assessments. Results: Significant improvements were observed in best-corrected visual acuity (BCVA) and central foveal thickness (CFT) at the end of the 12th week, with mean values of 0.79 ± 0.34 (range: 0.30–1.78) and 261.72 ± 58.13 (range: 201–433), respectively. Postoperatively, epiretinal membrane was detected in 14 (28%) patients, whereas external limiting membrane (ELM) disruption was noted in 8 (16.0%) patients. The percentage of photoreceptor inner segment/outer segment (IS/OS) disruption in RRD patients was 11 (22.0%), and 8 (16.0%) patients had subretinal fluid (SRF). Intraretinal fluid was absent in all patients postoperatively. Conclusion: High-resolution imaging by SD-OCT facilitates the interpretation of retinal anatomy and enables the detection of clinically nonevident structures. ELM disruption, IS/OS disruption, and the presence of SRF were associated with poor visual outcomes. While no statistically significant difference was found in the presence of SRF between macula-on and macula-off RRD patients, ELM and IS/OS disruption was observed only in macula-off RRD cases. Overall, macula-on patients showed improvements in BCVA and CFT at the end of the 12 weeks compared to macula-off RRD patients following RD surgery.